The effect of meditation on brain relaxation incorporating different physiological activities - Nurul Nabilah Abd Razak (Kulliyyah of Engineering,International Islamic University Malaysia, 2021)
Anxiety and depression have become such a widespread illness. It has been affecting people’s health which can lead to suicidal tendencies. According to the World Health Organization, every year close to 800 000 people take their own lives and there are also many more attempts of suicidal cases reported. It is due to an imbalance in the control of brain activities which relates to a lack of brain relaxation. Studies related to depression and stress with the nervous system had been conducted and Electroencephalogram signal is found to have the potential to detect brainwave signal in real-time data. Dissimilar physiological activities may react differently towards brainwave activities which will result in the various effects of brain relaxation. Therefore, this study was proposed to investigate the effect of meditation on brain relaxation incorporating different physiological activities. In this study, Electroencephalogram data were acquired from 12 subjects consisting of 6 males and 6 females aged ranged between 10-50 years old with normal health condition using the BrainLink device. Butterworth filter was applied to smoothen the signal. Later, based on the filtered signal, Alpha, Beta and Delta waves were segmented as the extracted features. For the final phase, the average value of amplitude differences and t-value test were conducted as to complete the decision making stage. All the signals utilized in this study were obtained from three set of experiments, which consisted of three physiological actions performed by the volunteers. The first activity was to sit at rest in the most comfortable position for three minutes. The second activity involved listening to and recitation along with a zikr (supplications) playlist (Allah, Ya Allah) for three minutes. Finally, the third activity involved the subjects walking for three minutes. Based on the average amplitude values, it was observed that different physiological activities caused diverse shape of the brainwave. Alpha waves were dominant as compared to other brain waves while sitting at rest in the first experiment. The second physiological activity, which is listening and reciting to the zikr, shows that delta wave is the most prevailing signal as compared to Alpha and Beta waves. As for the third experiment which is walking, the signals showed prominence in the Beta waves. Based on the t-value test, it was found out that for all the experiment the t values were less than 0.05 which obeys the t-test prediction. In other words, this study is a better alternative to the current approaches since it proves that zikr will change a person's state of brain to be more relaxed and tranquil. In a nutshell, this research has investigated the effects of meditation initiated through different physiological activities, on brain relaxation and has the potential to assist anxiety and stress patients to relax and stay calm.